(untitled) (Research, Society and Development, 2020)
In this study, the physicochemical characteristics of starch extracted from ten different cultivars of cassava roots, from different soils, were investigated. There are significant (p<0.05) variations in the proportion of starch damaged during extraction, even in samples of the same cultivar. Amylose content differs among cultivars and even within the same cultivar harvested in different soils (varying from 20.00 to 24.07%). According to the type of soil the starch samples showed distinct values for the crystallinity index. This indicates the need for the physicochemical characterization of starch samples to be carried out even when they originate from the same cultivar. The results obtained can be used as support tools for improvement of cassava genetics, optimizing the process of selection and maintenance of a genetic bank. The results, coupled with chemometric analyses (PCAs and clusters), allowed to distinguish cultivars according to their physicochemical and functional peculiarities, suggesting their potential to be used by industries and as food.